Rethinking of Coase Theorem: Externalities and Uncertainty - Kuzmin, Evgeny A.; Semyonovykh, Sergei M. (International Journal of Economics and Financial Issues, 2015)
A behaviour of economic agents in many respects depends on taking into account those conditions that have appeared around them. Traditionally, to such conditions, researchers have referred the uncertainty and factors of the institutional control, often projected on a value of the transaction costs. Studies in stimulants for any form of the agents’ behaviour lead us to an analysis of the Coase theorem, which is expected to explain a number of similar regularities. However, ambiguous approaches to the theorem interpretation generate conflicts in a perception and identification of externalities. It is a solution to this challenge, which is a focus of this research. In a critical review of works by Coase and his followers, the theorem statement has been made clearer; we have also put forward a hypothesis on an origin of the externalities and introduced additional criteria to identify them. The paper has given a scientific rationale for an author’s assumption that the utility of impure goods depends on the vector of the externalities, which ultimately determines the stratification in a field of the externalities (positive or negative). Keywords: Externalities; Coase Theorem, Uncertainty. JEL Classifications: Ð11; B25; B40